Management of the Librarian in Improving the Student’s Reading Interest in SMAN 1 Sungai Tarab - Armizawati Armizawati (IAIN Batusangkar, 2022)
The article that the researcher created serves to describe how the role of the librarian in increasing student interest in reading at SMAN 1 Sungai Tarab. In the new normal period, the management of the librarian has an important role in increasing student interest in reading at SMAN 1 Sungai Tarab. In an effort to increase student interest in reading, the head of librarianship needs to form an effective and optimal strategy. This study aims to examine the strategy of the librarian in increasing student interest in reading at SMAN 1 Sungai Tarab. The method used in this research is a qualitative approach with the type of phenomenology. In this study, in collecting the data needed to achieve the objectives of this study, the researchers used observation, interviews with the librarian of SMAN 1 Sungai Tarab, and also documentation. The results of the research that the researchers conducted showed that there were 2 special strategies for the head of the library at SMAN 1 Sungai Tarab in the process of increasing students' reading interest. The strategy chosen by the head of the library in this case is to form a young librarian, the library trolley (TROPUS). Recommendations and suggestions from this research are that the head of the Received: 11-01-2022; Revised: 15-02-2022; Accepted: 19-06-2022 58 AL-FIKRAH,Volume X Nomor 1, Juni 2022 library can cooperate with all staff and students in developing a new implementation-oriented strategy using TROPUS for all implementers in order to be able to increase students' reading interest with the new adequate facilities.